Two-Temperature Two-Dimensional Model of Underground Shale Heating by Electromagnetic Field; Advanced Materials Research; Vol. 1040 : High Technology: Research and Applications 2014 (HTRA 2014) - Martemyanov S. M. Sergey Mikhailovich (Simulation of Physical and Chemical Processes, 2014)
Title screen